Permafrost conditions in the Mediterranean region since the Last Glaciation - Oliva, Marc (2019)
The relatively warm climate conditions prevailing today in the Mediterranean region limit cold geomorphological processes only to the highest mountain environments. However, climate variability during the Late Pleistocene and Holocene has led to significant spatio-temporal variations of the glacial and periglacial domain in these mountains, including permafrost conditions. Here, we examine the distribution and evolution of permafrost in the Mediterranean region considering five time periods: Last Glaciation, deglaciation, Holocene, Little Ice Age (LIA) and present-day. The distribution of inactive permafrost-derived features as well as sedimentary records indicates that the elevation limit of permafrost during the Last Glaciation was between 1000 m and even 2000 m lower than present. Permafrost was also widespread in non-glaciated slopes above the snowline forming rock glaciers and block streams, as well as meter-sized stone circles in relatively flat summit areas. As in most of the Northern Hemisphere, the onset of deglaciation in the Mediterranean region started around 19-20 ka. The ice-free terrain left by retreating glaciers was subject to paraglacial activity and intense periglacial processes under permafrost conditions. Many rock glaciers, protalus lobes and block streams formed in these recently deglaciated environments, though most of them became gradually inactive as temperatures kept rising, especially those at lower altitudes. Following the Younger Dryas glacial advance, the Early Holocene saw the last massive deglaciation in Mediterranean mountains accompanied by a progressive shift of permafrost conditions to higher elevations. It is unlikely that air temperatures recorded in Mediterranean mountains during the Holocene favoured the existence of widespread permafrost regimes, with the only exception of the highest massifs exceeding 2500-3000 m. LIA colder climate promoted a minor glacial advance and the spatial expansion of permafrost, with the development of new protalus lobes and rock glaciers in the highest massifs. Finally, post-LIA warming has led to glacial retreat/disappearance, enhanced paraglacial activity, shift of periglacial processes to higher elevations, degradation of alpine permafrost along with geoecological changes.